Aflatoxin M1 Levels in Cheeses in Türkiye: A Review - Barış Ötün (Turkish Journal of Agriculture: Food Science and Technology)
Milk and dairy products mostly contain mycotoxins such as aflatoxin M1, aflatoxin M2, ochratoxin, cyclopiazonic acid, trichothecene, zearalenone, patulin. Mycotoxins in cheese are produced by certain types of fungi. These either directly contaminate the cheese or feed, or indirectly contaminate the milk used in cheese production. Aflatoxin, causes serious impacts on human and animal health, thus costs the world economy billions of dollars. The first legal regulation regarding aflatoxin M1 in Turkiye came into force in 1990. Subsequently, various legislations were published in 1997, 2002, 2008, 2011 and 2023. In this study, 60 publications were examined that investigate the presence of aflatoxin M1 in various cheeses in Turkiye in the last 50 years (1973-2023). In the studies, aflatoxin M1 was detected in almost all cheeses, and only a few were found in rates exceeding the Turkish Legal Limits. Researchers stated different limits for aflatoxin M1 in cheese. To minimize the presence of aflatoxin M1, the following recommendations should be considered. Developing new detection methods, enacting new legal regulations, increasing the frequency of legal inspections, improving the production, transportation and storage conditions of milk and dairy products, improving feed quality, increasing awareness of the health effects of aflatoxin M1.